The Role of Hypnotherapy in Reducing Anxiety and Enhancing Work Motivation among Employees: A Phenomenological Study of Clients at Rumah Terapi Kita Hypnotherapy Center: Peranan Hipnoterapi Dalam Mengatasi Kecemasan Dan Meningkatkan Motivasi Kerja Pada Karyawan; Studi Fenomenologis Klien Di Rumah Terapi Kita Hipnoterapi - Sofiana Dewi Indriati; Ajeng Tias Endarti; Lilis Heri Mis Cicih (Universitas Mohammad Husni Thamrin, 2026)
Mental health in the workplace plays a crucial role in sustaining organizational performance and productivity. Untreated anxiety can impair concentration, reduce motivation, and diminish work effectiveness. Hypnotherapy has emerged as a potential alternative intervention to address these challenges, although its application in Indonesia remains limited. This study aims to explore the subjective experiences of employees undergoing hypnotherapy, particularly in relation to reducing anxiety and enhancing work motivation.Method: Using a qualitative phenomenological approach, six informants were selected based on their General Anxiety Disorder-7 (GAD-7) scores. Data were collected through in-depth interviews, observations, and documentation at Rumah Terapi Kita Hypnotherapy in July 2025. Thematic analysis was applied, with validity ensured through source triangulation and member checking. The findings reveal that before therapy, employees experienced anxiety symptoms such as sleep disturbances, fatigue, difficulty concentrating, and decreased motivation. During hypnotherapy, participants reported deep relaxation, reduced negative thoughts, and a sense of calm. After therapy, anxiety levels significantly declined, work motivation increased, concentration and sleep quality improved, and emotional regulation became more stable.This study concludes that hypnotherapy is an effective, efficient, safe, and sustainable alternative intervention for alleviating anxiety and enhancing work motivation. These findings are expected to serve as a valuable reference for practitioners, organizations, and future research in developing workplace mental health programs.